2005
DOI: 10.1103/physrevd.71.086006
|View full text |Cite
|
Sign up to set email alerts
|

Spacelike boundaries from thec=1matrix model

Abstract: We find classical solutions of two dimensional noncritical string theory which give rise to geometries with spacelike boundaries, similar to spacetimes with cosmological event horizons. In the c = 1 matrix model, these solutions have a representation as simple time dependent configurations. We obtain the causal structure of the resulting spacetimes. Using the macroscopic loop transform, we probe the form of the tachyon condensate in the asymptotic regions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 28 publications
0
48
0
Order By: Relevance
“…The present paper deals with one particular background in [1]. The methods and results are, however, expected to be similar for the other backgrounds discussed in that paper.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present paper deals with one particular background in [1]. The methods and results are, however, expected to be similar for the other backgrounds discussed in that paper.…”
Section: Introductionmentioning
confidence: 99%
“…The same fact might also suggest that there is no well defined scattering problem. The analysis of [1] however showed that the "space" on which the closed string modes propagate is related to the space of eigenvalues in a non-trivial time dependent way. As a result, this closed string space is still of infinite extent at arbitrarily late times and there is indeed a well posed scattering problem.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations